Răspuns :
Răspuns:
17. a) 6x³+6x²-5x-5 totul supra 2x
b) -3x³-12x²+23x+12 totul supra 5
c) x²
d) 2x²-x
18. a) -2x²+4x+11
b) 2x²+6x+13
c) -7x²+14x-15
d) -2x²-1
Explicație pas cu pas:
17. a) 6x+(2x+3x+5-6x³+6x²)÷(-2x) =
= 6x+(5x+5-6x³+6x²)÷(-2x) =
= 6x+ 5x+5-6x³+6x²/-2x =
= 6x- 5x+5-6x³+6x²/2x =
= 12x²-(5x+5-6x³+6x²)/2x =
= 12x²-5x-5+6x³-6x²/2x =
= 6x²-5x-5+6x³/2x =
= 6x³+6x²-5x-5/2x
b) 3x-(8x²+12x-3x⁴-12x³)÷(-5x) =
= 3x+ 8x²+12x-3x⁴-12x³/5x =
= 3x+ x(8x+12-3x³-12x²)/5x =
= 3x+ 8x+12-3x³-12x²/5 =
= 15x+8x+12-3x³-12x²/5 =
= 23x+12-3x³-12x²/5 =
= -3x³-12x²+23x+12/5
c) x²-x+(2x²+4x-x²-4x)÷x =
= x²-x+x²÷x =
= x²-x+x =
= x²
d) (x³+x²-2x-x²+2x)÷x+x²-x =
= x³÷x+x²-x =
= x²+x²-x =
= 2x²-x
18. a) x³-x²+3x+2x²-2x+6-(x³+2x²-5x+x²+2x-5) =
= x³-x²+3x+2x²-2x+6-(x³+3x²-3x-5) =
= x³-x²+3x+2x²-2x+6-x³-3x²+3x+5 =
= -2x²+4x+11
b) 2x³-4x²+8x+x²-2x+4-(2x³+x²+3x-6x²-3x-9) =
= 2x³-4x²+8x+x²-2x+4-(2x³-5x²-9) =
= 2x³-4x²+8x+x²-2x+4-2x³+5x²+9 =
= 2x²+6x+13
c) x³-3x²+2x-3x²+9x-6-(x³-2x²+3x+3x²-6x+9) =
= x³-3x²+2x-3x²+9x-6-(x³+x²-3x+9) =
= x³-3x²+2x-3x²+9x-6-x³-x²+3x-9=
= -7x²+14x-15
d) -2x³+2x²-4x+x²-x+2+2x³-2x²+2x-3x²+3x-3 =
= 0-2x²-1 =
= -2x²-1